Rising sea level, temperature, and precipitation impact plant and ecosystem responses to elevated CO2 on a Chesapeake Bay wetland: review of a 28‐year study. (11th June 2014) - Drake, Bert G.
Abstract An ongoing field study of the effects of elevated atmospheric CO2 on a brackish wetland on Chesapeake Bay, started in 1987, is unique as the longest continually running investigation of the effects of elevated CO2 on an ecosystem. Since the beginning of the study, atmospheric CO2 increased 18%, sea level rose 20 cm, and growing season temperature varied with approximately the same range as predicted for global warming in the 21st century. This review looks back at this study for clues about how the effects of rising sea level, temperature, and precipitation interact with high atmospheric CO2 to alter the physiology of C3 and C4 photosynthetic species, carbon assimilation, evapotranspiration, plant and ecosystem nitrogen, and distribution of plant communities in this brackish wetland. Rising sea level caused a shift to higher elevations in the Scirpus olneyi C3 populations on the wetland, displacing the Spartina patens C4 populations. Elevated CO2 stimulated carbon assimilation in the Scirpus C3 species measured by increased shoot and root density and biomass, net ecosystem production, dissolved organic and inorganic carbon, and methane production. But elevated CO2 also decreased biomass of the grass, S. patens C4. The elevated CO2 treatment reduced tissue nitrogen concentration in shoots, roots, and total canopy nitrogen, which was associated with reduced ecosystem respiration. Net ecosystem production was mediated by precipitation through soil salinity: high salinity reduced the CO2 effect on net ecosystem production, which was zero in years of severe drought. The elevated CO2 stimulation of shoot density in the Scirpus C3 species was sustained throughout the 28 years of the study. Results from this study suggest that rising CO2 can add substantial amounts of carbon to ecosystems through stimulation of carbon assimilation, increased root exudates to supply nitrogen fixation, reduced dark respiration, and improved water and nitrogen use efficiency.